RhD-negative blood donors: genetic polymorphisms and testing strategies - WANG Kecheng; WANG Xiaoqin; DING Yingzhou; ZHANG Tingting; LIU Ming; XU Cheng (Zhongguo shuxue zazhi)
[Objective] To investigate the genetic basis of RhD-negative phenotype in the blood donor population of Nantong City. [Methods] RHD genotyping was performed on 386 randomly selected RhD-negative donor samples (from a total of 676 RhD-negative donors identified between January 20, 2023, and June 28, 2024) using polymerase chain reaction (PCR), and the inconclusive results were confirmed by nucleotide sequencing. [Results] Ten RHD allele types were identified: The complete deletion variant RHD* 01N.01 was predominant (64.25%, 248/386); followed by RHD* 01EL.01 (19.69%, 76/386). RHD* 01N.03, RHD* 01N.04, RHD* 01N.16 and RHD* 01EL.32 were frequently observed., RHD* 01EL.02, RHD* 01EL.08, RHD* 01EL.37 and RHD* 01N.25 were rare, and two exon deletion variants remained uncharacterized. The phenotypic distribution of RhD-negative blood donors was ccee (55.44%)>Ccee(31.09%)>ccEe(5.96%)>CCee(5.44%)>CcEe(1.81%)>CcEE(0.26%), and the antigen distribution trend was e(99.74%)>c(94.56%)>C(38.60%)>E(8.03%). A correlation was observed between RHD genotypes and RhCE phenotypes. [Conclusion] The Nantong blood donor population exhibits unique RHD gene polymorphisms. Integrating RhCE serological phenotyping with RHD genotyping is essential for ensuring transfusion safety.